2019
DOI: 10.1111/jonm.12741
|View full text |Cite
|
Sign up to set email alerts
|

The impact of restricted decision‐making autonomy on health care managers’ health and work performance

Abstract: Aim The aim of this study was to investigate how restricted decision‐making autonomy and conflicting demands impact operational managers’ work performance and health. Background Managers at operational level (first‐ and second‐line managers’) in health care organisations are commonly exposed to strain in their work situation with high demands and a challenging work context. Although they play an important role, the knowledge about the causal associations between stressful job demands and their consequences is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
3
16
0
1
Order By: Relevance
“…By sharing their knowledge and experience with their colleagues, they come up with creative solutions for problems/issues. These findings are line-up with the findings of Fallman et al (2019), who confirmed that individuals at health-care institutes having KS behavior were innovated during their work and searched for novel techniques to improve their performance. The study, thus, made an important contribution by understanding how sharing ones' knowledge, ideas and experience-in form of creating a social circle and perceived benefits from each other-is important in fostering their job activities that contribute to the hospitals' technical core.…”
Section: Discussionsupporting
confidence: 82%
“…By sharing their knowledge and experience with their colleagues, they come up with creative solutions for problems/issues. These findings are line-up with the findings of Fallman et al (2019), who confirmed that individuals at health-care institutes having KS behavior were innovated during their work and searched for novel techniques to improve their performance. The study, thus, made an important contribution by understanding how sharing ones' knowledge, ideas and experience-in form of creating a social circle and perceived benefits from each other-is important in fostering their job activities that contribute to the hospitals' technical core.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, devolved HR responsibilities are an emerging burden facing managers and are often done poorly (Podger, 2017). ER may help managers balance both people- and task-oriented work, such as administration, work process management and improvement, and employee development and support (Fallman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Managerial support involves providing emotional support, looking for creative solutions that meet both organizational and employee needs as well as facilitating flexible work practices (Hammer et al, 2009). Nonetheless, nurse managers also have limited decision-making ability as they work within the constraints of broader organizational goals and limited resources (Fallman et al, 2019). Generally, employees who report more supervisor support also report lower WFC (Allen et al, 2000;Kossek et al, 2011;Hammer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%